Optimization of the Multi-element Synthetic Transmit Aperture Method for Medical Ultrasound Imaging Applications - TASINKEVYCH, Yuriy; TROTS, Ihor; NOWICKI, Andrzej; LEWANDOWSKI, Marcin (Archives of Acoustics, 2013)
The paper presents the optimization problem for the multi-element synthetic transmit aperture method (MSTA) in ultrasound imaging applications. The optimal choice of the transmit aperture size is made as a trade-off between the lateral resolution, penetration depth and the frame rate. Results of the analysis obtained by a developed optimization algorithm are presented. The maximum penetration depth and lateral resolution at given depths are chosen as optimization criteria. The results of numerical experiments carried out in MATLABr using synthetic aperture data of point reflectors obtained by the FIELD II simulation program are presented. The visualization of experimental synthetic aperture data of a tissue mimicking phantom and in vitro measurements of the beef liver performed using the SonixTOUCH Research system are also shown.